E3 ubiquitin ligases and deubiquitinases in bladder cancer tumorigenesis and implications for immunotherapies - Wang, Maoyu; Zhang, Zhensheng; Li, Zhizhou; Zhu, Yasheng; Xu, Chuanliang (Frontiers in Immunology, 2023)
With the rapidly increasing incidence of bladder cancer in China and all over the world, great efforts have been made to understand the detailed mechanism of the tumorigenesis of bladder cancer. Recently, the introduction of immune checkpoint inhibitors based immunotherapy has changed the treatment strategy for bladder cancer, especially for the advanced bladder cancer and improved the survivorship of patients.The ubiquitin-proteasome system, which impacts a lot of biological processes, plays an important role in bladder cancer. Several E3 ubiquitin ligases and deubiquitinases target immune checkpoint directly or indirectly. In this review, we summarize the recent progress of E3 ubiquitin ligases and deubiquitinases in bladder cancer tumorigenesis and further highlight the implications for bladder cancer immunotherapies.Bladder cancer (BCa) is one of most commonly types of cancer, with 550,000 new cases and 200,000 deaths annually(1). While the 5-year survival rate of all bladder cancer patients is 77.1%, the rate drops dramatically to 36.3% for regional disease and 4.6% for metastatic disease(2). Therefore, adjunctive therapy to improve prognosis in